First implementation of MOOC for basic one health training to control zoonoses in Indonesia - Putra, Luqman Suyanto; Kustandi, Cecep; Wirasti, Murti Kusuma (Akademika, 2025)
Collaboration among health professions in controlling the spread of various infectious diseases is crucial for tracking and responding to zoonotic threats. The limited training that can be attended openly and massively to reduce cases of zoonotic diseases remains an unresolved issue. MOOC for One Health Basic Training is here to provide a solution to this problem. This research aims to describe the implementation of MOOC for One Health basic training, conducted for the first time in Indonesia. This research makes an important contribution by applying practical experience in training the One Health approach using the latest technology. 539 participants have registered, with a completion rate of 81%. Most participants are women from primary health care (puskesmas). Positive feedback was obtained with 94.6% of participants agreeing and strongly agreeing that they had a satisfying learning experience. By providing open and free learning, MOOC have met educational needs. Learning from the progress of online learning will help healthcare workers who are busy with their daily targets at work. This research shows that MOOC receive a positive response and can be applied in training in the health sector.